Combined experimental and theoretical investigation on photophysical properties of trans-azobenzene confined in LTL zeolite: Effect of cis-isomer forming - Wilaiporn Insuwan (2018)
The spectroscopic methods and molecular modeling were employed to study the photophysical properties of t-azobenzene in solution and in the channel of zeolite LTL. The effects of the interactions between the dye molecules and zeolite framework on the electronic states were examined experimentally by diffuse reflectance UV-visible absorption and fluorescence emission. The changes observed in the spectra were dependent on the forms of zeolite LTL (H-LTL and K-LTL). In addition the structural properties of the dye in the different environments were also intensively investigated by density functional theory (DFT) calculations with B3LYP/6-31G(d,p) level of theory. The 324T cluster model and the ONIOM (B3LYP/6-31G(d,p):UFF) methods were employed for the calculating the orientations of the dye in the zeolite system. The experimental data are consistent with the calculation results. The dye in solution can be relaxed into the planar structure, however, when the dye is in LTL zeolite it is constrained by the framework and is therefore twisted due to the confinement effects of zeolite. Moreover, emission spectra were detected only from protonated t-azobenzene incorporated into H-LTL while no emission was detected from t-azobenzene confined in K-LTL framework. The results of the study lead to the conclusion that the zeolite framework affects both the structural and photophysical properties of t-azobenzene. © 2014 Elsevier Inc. All rights reserved.